The discovery of penta-peptides inhibiting the activity of the formylglycine-generating enzyme and their potential antibacterial effects against Mycobacterium tuberculosis. Issue 29 (29th June 2022) - Asiimwe, Nicholas; Al Mazid, Mohammad Faysal; Jeong, Yong Taek; Lee, Juyong; Lee, Jun-Seok
Abstract : A penta-peptide, SMMMC, inhibits the activity of formylglycine-generating enzyme. Abstract : The formylglycine-generating enzyme is a key regulator that converts sulfatase into an active form. Despite its key role in many diseases, enzyme activity inhibitors have not yet been reported. In this study, we investigated penta-peptide ligands for FGE activity inhibition and discovered two hit peptides. In addition, the lead peptides also showed potential antibacterial effects in a Mycobacterium tuberculosis model.